2010
DOI: 10.1016/j.ejcts.2009.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Three decades of experience in the surgical multi-modality management of pleural mesothelioma

Abstract: In this series, cytoreductive surgery combined with post-operative adjuvant therapy provided better survival despite either advanced disease or surgically less fit patients. Thus, pleurectomy/decortication may be the procedure of choice, given that neither surgical procedure (EPP or PD) is not curative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 15 publications
1
52
0
Order By: Relevance
“…In the context of multimodal therapy, Cao et al [24], on the basis of their meta-analysis, concluded that selected patients who underwent extended P/D had lower perioperative morbidity and mortality with similar, if not superior, long-term survival compared with those who underwent EPP. Furthermore, Lucklatz and others [22] reported that P/D combined with postoperative adjuvant therapy provided better survival compared with EPP, irrespective of factors such as advanced disease or surgically less fit patients.…”
Section: Why Is Survival After P/d Equal To or Even Better Than That mentioning
confidence: 99%
“…In the context of multimodal therapy, Cao et al [24], on the basis of their meta-analysis, concluded that selected patients who underwent extended P/D had lower perioperative morbidity and mortality with similar, if not superior, long-term survival compared with those who underwent EPP. Furthermore, Lucklatz and others [22] reported that P/D combined with postoperative adjuvant therapy provided better survival compared with EPP, irrespective of factors such as advanced disease or surgically less fit patients.…”
Section: Why Is Survival After P/d Equal To or Even Better Than That mentioning
confidence: 99%
“…In the paper by Luckraz et al [21] the surgeon who first described surgical management of pleural mesothelioma in the 1970s (Butchart) is one of the authors. They describe their 30-year experience at their hospital.…”
Section: Resultsmentioning
confidence: 99%
“…A literature review evaluating reports in the last 10 years of outcomes after pleurectomy decortication demonstrates a median survival between 10 and 25 months (Table 1) (2,5,9,12,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Thirty-day mortality was between 0.0-6.8% across all studies.…”
Section: Discussionmentioning
confidence: 98%